Ley del Estado de la Florida para el avalúo tributario de tierras según su uso: Preguntas y respuestas sobre la Clasificación Agropecuaria en el Condado de Miami-Dade - Edward A. Evans; Mauricio Mosquera; Rodney L. Clouser; Jonathan Crane (EDIS)
Use-value assessment is the most widely used technique in the United States today for maintaining land in agricultural production. Although general guidelines are provided to Florida counties on the application of the state’s use-value assessment law, counties may vary slightly in the application and determination of the agricultural land’s value. Therefore, it is important for agricultural landowners to understand the guidelines used to determine value in the county where the land is assessed and taxed. This 6-page factsheet applies specifically to Miami-Dade County, Florida. Written by Edward A. Evans, Mauricio Mosquera, Rodney L. Clouser, and Jonathan Crane, and published by the UF Department of Food and Resource Economics, August 2011.